Rasa Percaya Diri Siswa pada Pembelajaran PAI Sekolah Dasar - Nofrianti, Lili; Wirdati, Wirdati (AS-SABIQUN, 2023)
This study aims to determine students' self-confidence in Islamic Religious Education Learning in Elementary Schools. This research was conducted at SD Negeri 20 Kurao Pagang. The approach used in this study is qualitative research with a type of research, namely case study research. Data collection techniques using observation, interviews and documentation. The research subjects were grade III students at SD Negeri 20 Kurao Pagang and Islamic Religious Education Teachers. Based on the results of the study, it can be concluded that the self-confidence of class III students at SD Negeri 20 Kurao Pagang is mostly optimal because it meets the criteria for indicators of self-confidence in PAI learning. Where, students believe in their own abilities, students are enthusiastic to ask questions and appear in front of the class during the learning process, and class III students at SD Negeri 2O Kurao Pagang are confident and speak calmly in expressing opinions when Islamic Religious Education learning activities take place.